Health and literacy: the Mini-Med School and the Literacy Foundation working together to reach native children - Clar, Monique; Chiasson, Sophie; Drouin, Éric; Seminaro, Bianca; Fagnant, Maryse (2016)
Également publié dans : Journal of the Canadian Health Libraries Association; vol. 37, no 2 The Mini-Med School (MMS) aims to motivate Native children to stay in school, introduce them to the health professions and encourage them to have healthy living practices. As reading skills play a major role in student retention, the MMS, in collaboration with the Health Library and the Literacy Foundation, is taking actions to facilitate children’s access to books. The MMS is a University program where health sciences students visit Native communities’ schools. The Health Library participates in those visits, develops book collections with the school libraries and recruits LIS students for the MMS book booth. The Literacy Foundation’s The Gift of Reading program aims to prevent reading and writing difficulties by giving books to underprivileged children. The MMS and the Library are joining forces with the Foundation to give children a better access to books. The medical librarian will continue working with the schools to upgrade the donated collections according to data on book usage and appreciation. MMS book collections will also be provided to three additional Native schools. On the other hand, The Gift of Reading program will now reach many Native children at home in those communities, by allowing them to receive a brand new book.